The Effect of Token Reinforcement on Reducing Symptoms of Attention Deficit Hyperactivity Disorders among Students with Learning Disabilities - Al-Zoubi, Suhail; Al-Qahtani, Mohammed (Jordan Journal of Educational Sciences, 2015)
The purpose of this study was to investigate the effect of Token reinforcement on reducing symptoms of attention deficit hyperactivity disorders (ADHD) among students with learning disabilities (LD). The sample of the study consisted of (17) LD students from Najran, Kingdom of Saudi Arabia. The sample was distributed randomly into two groups (control and experimental). Observation card was applied for the two groups through three stages: pretest, posttest, and follow-up test in order to calculate the symptoms of ADHD. The students in the experimental group received their teaching by using the token reinforcement for seven weeks, whereas the students in the control group received their teaching at the same time by the conventional way. Results revealed that there were statistically significant differences between the two groups' performance on the posttest, and follow-up test; favoring the experimental group. On the other hand, no statistically significant differences between the two groups' performance were attributed to the grade or type of learning disability